Life table of Macrolophus basicornis (Hemiptera: Miridae) preying on Myzus persicae (Sulzer) and Macrosiphum euphorbiae (Thomas) (Hemiptera: Aphididae) - Baños Díaz, Heyker Lellani; Louzada, Elaine; Moura, Nazare; Martínez Rivero, María de los Ángeles; Páez Bueno, Vanda Elena (Revista de Protección Vegetal, 2014)
Data obtained in studies on the biology and reproduction of Macrolophus basicornis(Heteroptera: Miridae) preying on Myzus persicae (Sulzer) and Macrosiphum euphorbiae (Thomas) on tomato at 28°C, were used to construct life tables for this polyphagous mirid. When M. euphorbiae waspreying on M. persicae, the net reproductive rate (Ro) was 4.75, the intrinsic rate of increase (rm) 0.02(hembra/hembra/day), the mean generation time (T) and the doubling time (DT) 73.91 and 32.9 days,respectively. The corresponding values when it was feeding on M. euphorbiae were 2.57, 0.01, 1.014 daysand 49.35 days, respectively. The results demonstrated that M. basicornis could survive and reproduce with M. persicae as well as M. euphorbiae as preys, although the number of females obtained by generation will be smaller with M. euphorbiae. The number of females increased twice in front of M. persicae, what demonstrated that this latter prey had greater acceptance by the predator. Key words: life table, Macrolophus basicornis, prey, Myzus persicae, Macrosiphum euphorbiae, tomato plants. TABLA DE VIDA DE MACROLOPHUS BASICORNIS (HEMIPTERA: MIRIDAE) TENIENDO COMO PRESAS A MYZUSPERSICAE (SULZER) Y MACROSIPHUM EUPHORBIAE (THOMAS) (HEMIPTERA: APHIDIDAE) RESUMEN: A partir de los datos obtenidos durante los experimentos de biología y reproducción de Macrolophus basicornis (Heteroptera: Miridae) se evaluaron las características de las tablas de vida del mirido usando como presa Myzus persicae (Zulser) y Macrosiphum euphorbiae (Thomas), en plantas a 28°C. Cuando la presa fue M. persicae la tasa neta reproductiva (Ro) fue 4,75 hijas hembras por cada madre, la tasa intrínseca de incremento (rm) fue de 0.02 (female/female/day, el tiempo medio generacional (T) y el doble tiempo generacional (DT) fueron de 73,91 y 32,9 días, respectivamente. Los valores correspondientes para M. basicornis cuando se alimenta de M. euphorbiae fue de 2,57, 0,01; 1,014 días y 49,35 días. Los resultados han demostrado que M. basicornis puede sobrevivir y reproducirse teniendo como presa tanto a M. persicae como a M. euphorbiae, aunque la cantidad de hembras obtenidas por generación será más pequeña teniendo como presa a M. euphorbiae; sin embargo, el número de hembras se incrementa dos veces cuando la presa es M. persicae, lo que demuestra que el depredador tiene mayor aceptación por esta presa. Palabras clave: tablas de vida, Macrolophus basicornis, presa, Myzus persicae, Macrosiphum euphorbiae, plantas de tomate.